Motor 3 Fasa Star Delta Menggunakan Outseal PLC (Programmable Logic Control) - Nurcholis, Adi; Thamrin, Nj.; Yusiana, Venny (Journal of Electrical Power Control and Automation (JEPCA), 2023)
With the development of science and technology, the use of electrical energy will continue to increase in households and industry. One of them is the use of a three-phase induction motor which is often used in industry in the production process. The many types of induction motors used require the selection of a more efficient system. The induction motor regulation system can be done manually or automatically. To automatically regulate the system, it can be done by applying programmable logic control (PLC). The aim of this research is to develop an automatic 3-phase electric motor control system using Outseal Programmable Logic Control (PLC).